Four Articles for Soviet Russia in the Journal „Dvuglavij orel“ (1921–1922) - Editors (Forum Theologicum Sardicense, 2025)
This paper analyzes four articles by Nikolay Glubokovski published in the journal "Dvuglavij Orel" (1921-1922). It discusses the historical context of these publications, their themes, and their significance within Glubokovski's work. The paper highlights the unique circumstances surrounding the publication and the lasting impact of these articles.